(3JWhjQ GdefXeGJ (B:s (3GdOdjd GdYdej dGYGOI GdgjcdI h GdJejR GdGOGQj h EOGQI GdJZjjQ (B/s - (3eGgQ, CMeOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2007)
(3eGgjI GdJWhjQ GdJfXjej h cja JJe YedjI GdJWhjQ GdJfXjej , GdJWhQ GdJGQjNj dfXQjGJ GdJWhjQ GdJfXjej h GdeSDhdhf Yfg , OQGSI GdhVY GdQGgf ef CLd GdJWhjQ GdJfXjej h cjajI JMOjO HOGFd GdJONd , GOGQI GdJZjjQ h GdJMhd ef GdNWI Gdi GdJfajP , GdQbGHI Ydi NWW GdJWhjQ GdJfXjej , CfhGY GdJONdGJ Ydi eSJhi GdaQO h GdhXjaI , Ydi eSJhi GdLeGYGJ h Ydi eSJhi GdGdefXeI ccd(B.s
Keywords: (3GdGOGQIs; (3GdJNWjWs; (3GdJfXjes